Global research on the utilization of population pharmacokinetic model: a bibliometric analysis from 2000 to 2024 - Yao, Yucheng; Zhang, Liyuan; Chen, Dan; Qin, Shiran; Meng, Mingyu; Guo, Qiuyan (Frontiers in Pharmacology, 2025)
Objective Population pharmacokinetic (PPK) model is capable of identifying the factors that influence the variability of pharmacokinetic (PK) profiles and the degree of their influence, effectively reduces unexplained variability, and demonstrates excellent predictive ability. PPK model has been successfully constructed in several populations for a variety of drugs. However, no study has yet conducted a bibliometric analysis of publications related to the PPK model. This study aims to provide a comprehensive overview of the research progress and hotspots in the field of PPK model research through bibliometric methods.MethodsA systematic search of the Web of Science database was conducted to collect articles and reviews related to the PPK model between 2000 and 2024. We then analyzed the data using Bibliometrix R package, Microsoft Office Excel, CiteSpace and VOSviewers.ResultsBetween 2000 and 2024, we identified a total of 6,125 papers and 128,856 citations. The average annual growth rate of the relevant publications was 10.35%, showing continued growth momentum. These research outputs are concentrated in North America, Western Europe, and East Asia, with USA leading the way with 2,340 publications and having the highest H-index (93) and total citations (54,965). Uppsala University and British Journal of Clinical Pharmacology are the institutions with the highest publication output and the most influential journals, respectively. Most of the funding agencies are from the USA and the subject categories for most publications are Pharmacology Pharmacy. In terms of author contributions, professor Karlsson MO is the leader in the field with 149 publications. In addition, wo found that “critically ill patients,” “tacrolimus,” “machine learning,” “external evaluation,” “polymyxin b,” “voriconazole,” “extracorporeal membrane oxygenation,” “dose optimization” and “model-informed precision dosing” are current research hotspots and future research trends.ConclusionThis study is the first comprehensive overview of the development of PPK model and research hotspots using bibliometric methods. Our findings provide researchers, especially beginners, with insights into the application area of PPK model, helping them to grasp key information in the field.